Sanctuary : a witch's tale. Season 2 [videorecording (DVD)] - Horsfield, Debbie, 1955- (AMC, 2026)
Set in a world in which witches live openly among humans, this suspenseful series is based on a novel and twists "Big Little Lies" with "Practical Magic." As fear and prejudice begin to unravel Sanctuary's fragile balance between magic and society, one woman must confront the forces threatening her community, her family and the truth itself.